THEORETICAL ISSUES REGARDING THE JUSTIFIABLE CAUSE FOR EXERCISING A RIGHT OR FULFILLING AN OBLIGATION - Alin-Sorin NICOLESCU; Mircea-Constantin SINESCU (Challenges of the Knowledge Society)
The review of the legal background, based on which was inserted in the time-specific normative acts, the justifiable cause under study indicates the legislator’s concern to provide some provisions removing the unjustifiable character of a criminal act. The legislator authoring the new Criminal Code emphasized that not all the causes removing the criminal character of an act are based on the absence of guilt. As regards justifiable causes, criminal law allows committing some acts that it itself forbids. In fact, in the context of some well-delimited states or circumstances, the unjustifiable character of a criminal act is removed, providing it the aspect of legality. The doctrine underlined the need for a regulation granting safety and certainty upon fulfilling their duties to the person enforcing the law, especially when, between such person and the law, an authority empowered to issue orders interposes itself; this means that such person should be aware that they are protected and defended against any liability, to the extent they fulfill their work-related duties in strictly legal conditions.